A hierarchical model of children’s research participation rights based on information, understanding, voice, and influence - Mayne, F.; Howitt, C.; Rennie, Leonie (2018)
© 2018, © 2018 EECERA. This paper introduces a hierarchical model of children’s (3- to 8-year olds) research participation rights that builds on work by Roger Hart and integrates key participation rights drawn from UNCRC Article 12: information, understanding, voice, and influence. It provides insight into the various levels of information that can be provided to children, the understanding that results, the scope given to them to express their views, and the degree to which their voices ultimately exert influence in research contexts. Each of these four elements plays a unique role in upholding and enhancing children’s rights in research and emphasises the need for rights to be woven into the fabric of a research project from its conception. Considering children’s rights of research participation in a more integrated manner, as suggested by the hierarchy, has the potential to improve participation experiences for children and to value them as citizens with meaningful rights.